Implementasi Sistem Pengelolaan Sampah di Tempat Pembuangan Sampah (TPS) Kepanjen Kabupaten Jombang - Firmansyah, Nosa Yudha; Widiyarta, Agus (Universitas Muhammadiyah Sorong, 2025)
The waste management issue in Jombang Regency, particularly at the Kepanjen Disposal Site, remains unresolved. This study aims to analyze the implementation of waste management policies at the site using a descriptive qualitative approach through field observation, in-depth interviews, and document analysis. The findings reveal four key aspects: (1) communication plays a crucial role but lacks coherence between planning and execution; (2) resource limitations, including budget, workforce, and infrastructure, serve as major obstacles despite long-term planning efforts; (3) field workers’ dedication deserves recognition, yet greater community participation is essential; and (4) the organizational structure, although legally established, has not been fully effective in practice. The study concludes that waste management at the Kepanjen Disposal Site requires an inclusive and collaborative approach emphasizing improved communication, resource allocation, human resource capacity, and multi-stakeholder cooperation to achieve sustainable waste management outcomes.